The Effect of Operational Costs, Capital Structure, Earnings Management, and Operating Cash Flow on Corporate Income Tax - Noviyanti, Cahyani Rahma; Sari, Imelda (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2024)
This research aims to examine the effect of operational costs, capital structure (proxied by the debt to equity ratio), earnings management, and operating cash flow on corporate income tax in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) during period 2018 to 2022. The research method used is quantitative, with secondary data in financial reports obtained from the website www.idx.co.id. The sampling method used a purposive sampling technique based on specified criteria. Ten companies with a research period of five years were obtained, and fifty research sample data were obtained. The analysis method used was multiple regression analysis using SPSS version 29. The results of this study show that operational costs have a significant positive effect on corporate income tax with a significance level of 0.002 < 0.05. Debt to equity ratio does not affect the amount of corporate income tax, with a significant level of 0.982 > 0.05. Earnings management does not affect the amount of corporate income tax with a significant level of 0.744 <0.05. Cash flow from operating activities has a significant positive effect on the amount of corporate income tax with a significance level of 0.001 < 0.05.